Severe infections after single umbilical cord blood transplantation in adults with or without the co‐infusion of CD34+ cells from a third‐party donor: results of a multicenter study from the Grupo Español de Trasplante Hematopoyético (GETH). Issue 2 (April 2015) - Martino, R.; Bautista, G.; Parody, R.; García, I.; Esquirol, A.; Rovira, M.; Cabrera, J.R.; Regidor, C.; Fores, R.; García‐Marco, J.A.; Serrano, D.; Barba, P.; et al.
Abstract: Background: Umbilical cord blood transplantation (CBT) is an established alternative source of stem cells in the setting of unrelated transplantation. When compared with other sources, single‐unit CBT (sCBT) is associated with a delayed hematologic recovery, which may lead to a higher infection‐related mortality (IRM). Co‐infusion with the sCBT of CD34 + peripheral blood stem cells from a third‐party donor (TPD) (sCBT + TPDCD34 + ) has been shown to markedly accelerate leukocyte recovery, potentially reducing the IRM. However, to our knowledge, no comparative studies have focused on severe infections and IRM with these 2 sCBT strategies. Methods: A total of 148 consecutive sCBT (2000–2010, median follow‐up 4.5 years) were included in a multicenter retrospective study to analyze the incidence and risk factors of IRM and severe viral and invasive fungal infections (IFIs). Neutrophil engraftment occurred in 90% of sCBT ( n = 77) and 94% sCBT + TPDCD34 + ( n = 71) recipients at a median of 23 and 12 days post transplantation, respectively ( P < 0.01). Results: The 4‐year IRM was 24% and 20%, respectively ( P = 0.7), with no differences at day +30 (5% and 4%, respectively) and day +100 (10% and 8%, respectively). In multivariate analysis early status of the underlying malignancy, cytomegalovirus (CMV)‐seronegative recipient and high CD34 + cell content in the cord blood unit before cryostorage (≥1.4 × 10 5 /kg) were protective of IRM. Among the causes of IRM, bacterial infections and IFIs were more common in sCBT (15% vs. 4%), while CMV disease and parasitic infections were more common in the sCBT + TPDCD34 + cohort (5% vs. 16%). Conclusion: These data show that sCBT supported with TPDCD34 + cells results in much shorter periods of post‐transplant leukopenia, but the short‐ and long‐term rates of IRM were comparable to those of sCBT, presumably because immune recovery is equally delayed in both graft types.